CONTENT MARKETING OF SPORTS ACTIVITIES AS A TOURIST INFLUENCE IN THE DESTINATION SUCRE - Zambrano , Lilia Moncerrate Villacis; Calderón, Jonathan Eudaldo Quezada (Seven Editora, 2025)
The main objective of the research was to evaluate how the content marketing of sports activities influences the tourist attraction towards the Sucre destination. The research used a quantitative and qualitative approach, a descriptive and exploratory design was used, the technique was the survey. , non-probabilistic sampling was chosen for convenience, to measure reliability and tabulate the data, the spss 26 program was used, giving a reliability of 0.979, it was concluded that content marketing applied to sports activities in Sucre was presented as a key strategy to enhance its tourist attraction, positioning the destination as a benchmark in dynamic and meaningful experiences. In addition, the integration of creative and authentic content linked to sporting events manages to attract visitors interested in unique experiences, promoting cultural interaction and the sustainable development of tourism, by linking sports promotion with the identity characteristics of the destination, Sucre is projected as an attractive and competitive place in the tourism market in the region, this combination of content marketing, sports and culture promotes local economic development , encourages community participation and reinforces the sense of identity, consolidating Sucre as a vibrant and constantly growing destination.DOI: https://doi.org/10.56238/sevened2025.021-072